2016
DOI: 10.1177/0748233715572562
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and genotoxic evaluation of different synthetic amorphous silica nanomaterials in the V79 cell line

Abstract: The nature of occupational risks and hazards in industries that produce or use synthetic amorphous silica (SAS) nanoparticles is still under discussion. Manufactured SAS occur in amorphous form and can be divided into two main types according to the production process, namely, pyrogenic silica (powder) and precipitated silica (powder, gel or colloid). The physical and chemical properties of SAS may vary in terms of particle size, surface area, agglomeration state or purity, and differences in their toxicity po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 31 publications
2
29
0
1
Order By: Relevance
“…In addition, the size increment from 20 to 70 nm importantly increased the viability levels, being more similar to those achieved by sub‐microparticles (SiPs ≥200 nm). These results are in agreement with previous findings describing that cytotoxicity generated by SiPs strongly depended on particle size and administered dose, with smaller silica particles producing a higher toxic effect (Guichard et al, ). Similar results were observed by McCarthy, Inkielewicz‐Stepniak, Corbalan, and Radomski () using 10, 150 and 500 nm SiPs in Calu‐3 cells.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the size increment from 20 to 70 nm importantly increased the viability levels, being more similar to those achieved by sub‐microparticles (SiPs ≥200 nm). These results are in agreement with previous findings describing that cytotoxicity generated by SiPs strongly depended on particle size and administered dose, with smaller silica particles producing a higher toxic effect (Guichard et al, ). Similar results were observed by McCarthy, Inkielewicz‐Stepniak, Corbalan, and Radomski () using 10, 150 and 500 nm SiPs in Calu‐3 cells.…”
Section: Discussionsupporting
confidence: 93%
“…Recent literature has reported on the cytotoxic and allergic effects of theses agents. Guichard et al (2015) reported cytotoxic and genotoxic effects in V79 cells exposed to 20-nm size amorphous silica that had been pre-dispersed in bovine serum albumin-water medium. Induction of allergen-specific T H 2-type allergic immune responses to nano-silica was reported by Yoshida et al (2011).…”
Section: Discussionmentioning
confidence: 99%
“…Data on the genotoxic properties of SAS, mostly assessed by the comet assay for detecting DNA damage or by the micronucleus assay for chromosomal damage, are however less clear. Generally, positive responses in genotoxicity assays are reported more frequently in vitro [5][6][7][8][9] than in vivo [10][11][12]. However, in vitro results remain quite variable and depend on the physical and chemical characteristics of the SAS and the cell type used.…”
Section: Introductionmentioning
confidence: 99%